Vapor-liquid-equilibria of fuel-nitrogen systems at engine-like conditions measured with Raman spectroscopy in micro capillaries - Klima, Tobias; Braeuer, Andreas S. (Fuel, 2019)
A fuel, here ethanol or decane, and nitrogen are fed at elevated pressure and temperature through a micro capillary of fused silica. The flow inside the capillary is characterized by alternating liquid- and vapor-phase segments that accommodate to thermodynamic equilibrium at the set temperature and pressure. The composition of the equilibrated liquid or vapor segments is measured in situ and remotely inside the micro capillary by Raman spectroscopy. Temperature-composition (Tx) vapor-liquid equilibria were measured for pressures between 3 MPa and 8 MPa and up to the highest mixture critical temperature of 593 K in this pressure range. Comparison to the scarce literature data for these conditions and to the GERG-2008 model, resembling the conditions in IC-engines at the time of injection, is shown.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Capillary; Fuel; Liquid; Raman spectroscopy; Solubility; Vapor; VLE